Evaluation of TMJ articular eminence morphology and disc patterns in patients with disc displacement in MRI - Hirata,Fabio Henrique (2007)
The aim of this study was to assess the shape of the temporomandibular joint (TMJ) articular eminence and the articular disc configuration and position in patients with disc displacement. TMJ magnetic resonance images (MRI) of 14 patients with bilateral disc displacement without unilateral reduction were analyzed. Articular eminence morphology was characterized as box, sigmoid, flattened, or deformed. Articular disc configuration was divided into biconcave, biplanar, biconvex, hemiconvex or folded, and its position, as "a" (superior), "b" (anterosuperior), "c" (anterior) or "d" (anteroinferior). The images were divided and the sides with disc displacement with reduction (DDWR) and without reduction (DDWOR) were compared. Regarding articular eminence shape, the sigmoid form presented the greatest incidence, followed by the box form, in the DDWR side, although this was not statistically significant. In the DDWOR side, the flattened shape was the most frequent (p = 0.041). As to disc configuration, the biconcave shape was found in 79% of the DDWR cases (p = 0.001) and the folded type predominated in 43% of the DDWOR cases (p = 0.008). As to disc position, in the DDWR side, "b" (anterosuperior position) was the most frequent (p = 0.001), whereas in the DDWOR side, "d" (anteroinferior position) was the most often observed (p = 0.001). The side of the patient with altered disc configuration and smaller shape of TMJ articular eminence seems to be more likely to develop non-reducing disc displacement as compared to the contralateral side.